Tetrahydrocannabinol vape-associated cannabis arteritis in a patient with minimal tobacco exposure - Morgan Colling, BS; Yousef Souri, MD; Thomas Reifsnyder, MD (Journal of Vascular Surgery Cases and Innovative Techniques)
Thromboangiitis obliterans (TAO) is an inflammatory vasculopathy that often presents in young men with substantial tobacco use. Cannabis arteritis is the cannabis-associated counterpart, but there remains controversy over its classification due to overwhelming concurrent tobacco use. A 31-year-old man developed lifestyle-limiting claudication that coincided with vaping high-potency tetrahydrocannabinol. Notably, his tobacco exposure was limited to a remote history of <1 pack-year. His claudication considerably improved after 4 weeks of cannabis cessation. This case demonstrates a rare instance of cannabis arteritis without concurrent tobacco use, suggesting cannabis may act as an independent causative agent of a distinct thromboangiitis obliterans-like arteritis.